Modern Watercolor : a playful and contemporary exploration of watercolor painting. - Van Leuven, Kristin (Modern series., 2017)
From beautifully dynamic leaves, flowers, and trees to simple geometric shapes and patterns, Modern Watercolor provides a contemporary, colorful, and fun approach to working in this timeless medium.